Etiology and risk factors associated with a pruritic papular eruption in people living with HIV in India. Issue 1 (3rd September 2013) - Farsani, Terry T; Kore, Sachin; Nadol, Patrick; Ramam, Mandalaparthy; Thierman, Sara J; Leslie, Kieron; Chandrasekar, Chockalingam; Sikhamani, Rajasekaran; Manoharan, Gurusamy; Kubba, Asha; Maurer, Toby A
Abstract : Introduction: Papulopruritic eruption (PPE) occurs in people living with HIV in India. Understanding the risk factors associated with this disease may help decrease the prevalence of PPE. Methods: This study was a case‐control study performed at the Government Hospital of Thoracic Medicine, a tertiary care hospital in Chennai, India. Cases included HIV‐positive, antiretroviral (ARV) therapy‐naïve adults experiencing a pruritic skin eruption for longer than one month, with evidence of multiple papular or nodular lesions and biopsy consistent with arthropod bite. Controls included HIV‐positive, ARV‐naïve patients without active skin rash. Main outcome measures were CD4 cell count, histology, and environmental exposures. We performed statistical analysis using Epi Info version 3.5.1 and SPSS version 11.0 (SPSS Inc., Chicago, IL). Categorical variables such as gender, urban versus rural residence, occupation, treatment history, CD4 count, use of insect repellents, and environmental exposures were evaluated using the χ 2 test (or the Fisher exact test when an expected value for a category was less than 5). The t ‐test was used to evaluate differences in age and the duration since HIV diagnosis. The Mann‐Whitney test was used to compare non‐normally distributed values such as CD4 cell count. A p ‐value that was less than 0.05 was considered to be statistically significant. Results: Forty‐one cases and 149 control subjects were included. Subjects with PPE had significantly lower CD4 cell counts compared to controls (225.5 cells/µL vs. 425 cells/µL; p =0.0001). Sixty‐six percent of cases had a CD4 cell count less than 350 cells/µL. PPE cases were less likely to use mosquito repellent techniques (odds ratio 2.81, CI = 1.45–5.45). Discussion: PPE may be an altered and exaggerated immune response to arthropod bites in HIV‐positive patients. CD4 cell count is significantly lower in patients with PPE, and therefore it may be considered a qualifying clinical finding for ARV initiation in resource‐poor settings. Protective measures against mosquito bites appeared to be important in preventing PPE in subjects at risk.